Antithrombin supplementation and risk of bleeding in patients with sepsis-associated disseminated intravascular coagulation. Issue 145 (September 2016) - Iba, Toshiaki; Gando, Satoshi; Saitoh, Daizoh; Wada, Hideo; Di Nisio, Marcello; Thachil, Jecko
Abstract: Introduction: Although antithrombin is commonly used for the treatment of sepsis-associated disseminated intravascular coagulation (DIC) in Japan, the factors influencing the incidence of bleeding complications have not been sufficiently studied. The purpose of this survey was to identify the factors that predict clinically relevant bleeding in patients receiving antithrombin for DIC. Methods: We analyzed data from 1026 sepsis-associated DIC patients with a baseline antithrombin activity ≤ 70% who underwent antithrombin supplementation at two dosages (1500 IU/day or 3000 IU/day) for three consecutive days. The patients' demographic characteristics, parameters before and after the treatment, and co-administered anticoagulants were analyzed in relation to the bleeding events. Results: Overall, 55 patients (5.36%) experienced bleeding events (major bleeding: 1.75%). Logistic regression analysis revealed that sustained DIC > 7 days was significantly associated with bleeding (odds ratio: 2.761, P  = 0.001). In contrast, the higher dose of antithrombin or the co-administration of recombinant thrombomodulin or heparins were not associated with bleeding events. Conclusion: A higher dose of antithrombin or the concomitant use of other anticoagulants were not associated with bleeding events. On the other hand, sustained DIC lasting more than one week was associated with an increased risk of bleeding in patients with sepsis-associated DIC. Highlights: Bleeding event was recognized in 5.36% (major 1.75%) with antithrombin substitution. Sustained DIC is the strongest risk factor of bleeding in sepsis-associated DIC. Bleeding was not increased by higher dose (3000 IU/day) of antithrombin. Bleeding was not increased by the co-administration of recombinant thrombomodulin.